Induction of somatic embryogenesis in Perezia coerulescens Wedd, medicinal plant highland - Olivera Gonzales, Percy (2019)
Perezia coerulescens, a native peruvian species, is used as tranquilizer in folk medicine and considered vulnerable status due extensive collection for its commercialization. Then, the aim of this research was obtain somatic embryos as alternative for its multiplication.Leaves, roots, rhyzomes, small shoot (15 – 20 mm) and big shoot (25 – 30 mm) from plants culture in vitro were grown using MS½ culture medium with sucrose (2%), agaragar (0,75%), 16 hours of light, 16 – 20 ºC, supplemented with NAA (2 mg/L), 2, 4-D (0,2; 1 and 2 mg/L) and without hormone. It was found that NAA (2 mg/L) and 2, 4-D (2 mg/L) induced callogenesis in 100% of small shoot and big shoot at two months, likewise 2, 4-D (1 mg/L) induced 100% of callogenesis of small shoot and big shoot at four months. However, embryogenic callus 2, 4-D (2 mg/L) treatment was fenolized at four month. Considering callus size and number of germinated somatic embryos, the best treatment to embryonics somatic was NAA (2mg/L) at four moth of culture and using small explants